FINNISH REGIONAL LOBBYING: A Study of Goals Means and Methods of Four Regional Lobbying Organisations - Pasanen, Ari Pekka (2018)
Lobbying has nowadays become almost a trend-word and is used quite freely also in standard language. But from where does lobbying originate and especially how does lobbying take place? This study concentrates on Finnish regional lobbying and illustrates the embodiment and meaning of lobbying as a means of influencing. Alongside power of the European Union has increased also influence of regions. Regions that may have only little influence on national level can have plenty of it on the European field if they just know the right means and methods. In this study will be described Finnish lobbying taking place in Brussels, goals of Finnish regions, and means that they use in their supervision of interests. This study clarifies the most important themes of Finnish lobbying and illustrates with real life examples how regions supervise their interests. In aggregate this study draws a picture of Finnish supervision of interests and its varying as-pects, and helps to understand what Finnish actors can achieve by lobbying. Another important objective is to describe lobbying processes and issues relating to them. Theoretical framework of this study bases on pluralism which lays a foundation for examination of lobbying. Lobbying for one is examined through some key terms that are decisions and procedures. Decisions involve questions concerning goals and goal-settings as well as targets and means on which are focused in lobbying. The latter, procedures discusses methods of lobbying and distinguishes two strategies: co-operation and competition. Data for this study is sought from subject discussing literature, newspaper articles and Internet sources. Empirical part for one bases on interviews of lobbying specialists. Finnish regional lobbyists that are the research subjects of this study operate in many respects according to a similar format. Targets of lobbying are to a great extent the same like also the methods used. The biggest differences are found in themes of supervision of interests, but there are differences also between partners that regions have. One important thing that divides Finnish regions is EU regional and structural policy and division into Objective 1 and 2 –regions. In the European scale East and North Finland are sparsely populated regions which are eligible to greater financial support than South and West Finland within the structural fund –programme. But instead of great differences this study will rather show that Finnish regional supervision of interests has more common denominators. Another significant issue that is discussed is the course of lobbying processes. There will be given an answer to for example following questions: What kind of means and methods do regional lobbyists use, what is a good lobbyist like, and what are the challenging sides of lobbying? In addition will be discussed the future of lobbying. The importance of lobbying will increase in the future, and therefore it will become even more important to know what lobbying is and what can be achieved by lobbying. Although it has already been repeated over and over again in varying contexts, also the findings of this study prove that the EU and varying actors operating round it should be brought closer to common people. There are several kinds of possibilities to influence and utilise the EU, but if those possibilities are not known benefits are in a way wasted. fi=Kokotekstiversiota ei ole saatavissa.|en=Fulltext not available.|sv=Fulltext ej tillgänglig.